Pedoman Hakim Dalam Mengadili Permohonan Perkara Dispensasi Kawin Menurut PERMA No. 5 Tahun 2019 - Burhanuddin Abd. Gani; Putri Ramadhani; Nahara Eriyanti (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2021)
In the Regulation of the Supreme Court of the Republic of Indonesia No. 5 of 2019 concerning Guidelines for Adjudicating Applications for Marriage Dispensation, article 15 letter (d) states that examining a child for whom a marriage dispensation is requested may seek a recommendation from a psychologist or professional Social Worker Doctor/Midwife, Social Welfare Personnel, Integrated Service Center for the Protection of Women and Children (P2TP2A). , Indonesian/Regional Child Protection Commission (KPAI/KPAD). However, in reality the implementation of the Banda Aceh Syar'iyah Court's decision with Case number 5/Pdt.P/2021/Ms.Bna, the Judge granted the petition for a marriage dispensation by the applicant without fulfilling the conditions stated in article 15 in letter (d). In addition, in the community, parents who marry off their children have not reached the age stipulated by law, and without a recommendation letter from a doctor, even though it is very important for the reproductive health of the prospective bride. The question in this thesis research is the first dispensation for marriage according to PERMA No. 5 of 2019 concerning guidelines for adjudicating applications for dispensation for marriage against underage women, and the second consideration of the judges of the Banda Aceh syar'iyah court in granting requests for dispensation for marriage to underage women. This study uses a qualitative method. The results of the study found that the marriage dispensation according to PERMA No. 5 of 2019 regarding guidelines for adjudicating applications for dispensation for marriage is that the application can be submitted for those who are not of the age in accordance with statutory regulations no. 16 of 2019 regarding amendments to law no. 1 of 1974. And the judge's consideration in granting the application for dispensation for marriage without fulfilling the conditions stipulated in PERMA No. 5 of 2019 in article 15 letter d because these conditions are supporting conditions, this can be seen from the age of the applicant because of concerns that occur in the reproduction of the woman because she is still a minor.